Generasi Emas Tangguh Tsunami: E-Komik dan Animasi Mengubah Ketakutan menjadi Kekuatan untuk Masa Depan Bandar Lampung - Sundari, Susanti; Carolina, Thabita; Suryani, Suryani; Aziz, Kholid; Fauzan, Haroni; Sari, Indah Purnama (Unri Conference Series: Community Engagement, 2024)
This Community Partnership Empowerment (PKM) activity aims to provide tsunami disaster mitigation education in Elementary Schools in 7 Districts through socialization and training, where the delivery of disaster themes is given in an interesting way using e-comic media and animated films about tsunamis. This is done to build the preparedness of the golden generation of Indonesia who are pro-active in prevention efforts to reduce disaster risks. The method used is Community Capacity Building or increasing community capacity to help improve community capabilities. The results of the activity showed an increase in participants' understanding of tsunamis (before 28.33% and after socialization 100%). In the training, there was an increase in participant skills (previously not competent: 0% and after training 100%). The activity received a very good response, participants were very enthusiastic and active in every activity. This activity was able to increase participants' understanding and knowledge which is to change fear into strength by being ready so that they are responsive and resilient in facing the threat of a tsunami.